ANALISIS PUTUSAN HAKIM PENGADILAN NEGERI KLATEN ATAS TERDAKWA PENYALAHGUNAAN NARKOTIKA (Studi Kasus/Perkara Tahun 2012-2014) - SUGIYONO, AGUS (Dinamika Hukum, 2016)
The objectives of this research are to study or analyze the legal consideration of the judges of Klaten District Court in implementing SEMA of the Republic of Indonesia Number 04 of 2010 and to study or analyze the legal consideration of the judges of Klaten District Court for not implementing SEMA of the Republic of Indonesia Number 04 of 2010. The background of the research is the ignorance or not implementing stipulation of SEMA of the Republic of Indonesia Number 04 of 2010 that causes the victims of narcotics abuse and addict suffered disadvantage and their rights are violated, because they should obtain the right of having rehabilitation in order to be cured from their addiction, but in fact, they are imprisoned. If the problem goes on, there will be legal violation and human right violation. The method of the research is juridicial normative research or library research, which is a research studying secondary data in the forms of legal regulation, courtverdict, legal theories and scholars’ opinions. The object of study is law as norm, in this case is the Judges’ Verdictas norm in effect for the parties imposed with sentence, nevertheless, this research will be completed with primary data which are interviews with the judges who handle the cases of narcotics abuse. The results of this research are: If, based on evidences and facts revealed in the trial, the defendantsare proved meeting all classifications of narcotics abuse or addict as stipulated in stipulation of SEMA RI Number 04 of 2010, the Defendants must be imposed with sentence of having rehabilitation, the obligation of judges to implement SEMA on the Defendants who have met classification of narcotics users or addicts, the juridicial consequence is that there is no another legal reason except a must to implement the stipulation of SEMA, meanwhile, the Judges who ignore it by excluding it in the legal consideration areconsidered as putting the Defendants into disadvantage because of violating the Defendants’ rights, the Judges’ action also contravene Article 197 paragraph (1) point d of KUHAP jo. Article 24 point a of the 1945 Constitution jo. Article 79 of Act Number 14 of 1985 concerning the Supreme Court jo. SEMA Number 04 of 2010 concerning the Placing of Narcotics Abuse, Abuse Victims and Narcotics Addicts into Medical Rehabilitation Center and Social Rehabilitation Center jo. Act Number 35 of 2009 Concerning Narcotics. Keywords : The Implementation of SEMA RI Number 04 of 2010.